2022
DOI: 10.55927/jpmb.v1i7.1607
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kemampuan Masyarakat dalam Pertolongan Pertama Gigitan Ular

Abstract: Gigitan ular berbisa merupakan kegawatdaruratan yang telah diketahui secara global, terutama terjadi pada wilayah tropis dengan pekerjaan utamanya petani, nelayan, pemburu, dan pawang ular. Tujuan dari pengabdian masyarakat ini adalah untuk meningkatkan pengetahuan dan kemampuan masyarakat dalam pertolongan pertama gigitan ular. Responden dalam penelitian ini sejumlah 40 orang diambil dengan tekhnik Purpossive Sampling. Setelah dilakukan kegiatan pengabdian masyarakat ini, pengetahuan dan kemampuan masyarakat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…Still, after being given training, the majority of respondents, namely 78%, demonstrated good knowledge behavior in handling snakebite wounds. This is also supported by research (Rachmania & Ludyanti, 2022); the ability of farmers to first aid for snake bites before being given counseling shows results of 52.5% in the less category, and the ability of the community after being given health education shows results for almost all respondents (87.5%) is in the good category.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Still, after being given training, the majority of respondents, namely 78%, demonstrated good knowledge behavior in handling snakebite wounds. This is also supported by research (Rachmania & Ludyanti, 2022); the ability of farmers to first aid for snake bites before being given counseling shows results of 52.5% in the less category, and the ability of the community after being given health education shows results for almost all respondents (87.5%) is in the good category.…”
Section: Discussionsupporting
confidence: 55%
“…This is supported by another journal, which states that based on their age, farmers are adults with a median age of 40; the majority are male, have worked as farmers for 12 years, and have a high school education background (Yunanto et al, 2022). However, another study that took respondents from farming communities found respondents aged 25-35 years, with the majority having no school education (Rachmania & Ludyanti, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Gigitan hewan yang memiliki bisa baik ular maupun hewan yang mentransmisikan virus rabies adalah kasus yang umum dan banyak terjadi di masyarakat terutama masyarakat dengan lingkungan yang banyak ular dan pembawa virus rabies seperti anjing, kucing dan hewan liar lainnya (Muthmainnah, 2020;Rachmania and Ludyanti, 2022). Gigitan ular dan hewan rabies bisa berbahaya sekali karena dalam beberapa menit akan terjadi kekurangan oksigen secara general atau menyeluruh sehingga hanya dalam hitungan menit klien akan kehilangan reflek nafas, denyut jantung dan kematian secara permanen dari batang otak (Afni and Sani, 2020).…”
Section: Pendahuluanunclassified